Analysis of the marina industry in Singapore. - Mak, May Chee. (2008)
The objectives of this study were as follows: 1) To evaluate the marina industry structure and its attractiveness; 2) To analyze and gain an insight to the management and operations of marinas and issues faced by marinas in Singapore; 3) To identify the important attributes of a successful marina.